The multidimensional peer victimization scale: a systematic review - Joseph, Stephen; Stockton, Hannah (Elsevier, 2018)
Developing bullying interventions and testing their success depends on the valid and reliable measurement of peer victimization. The objective of this study was to examine the psychometric properties of the Multidimensional Peer Victimization Scale (MPVS, Mynard & Joseph, 2000). This systematic review examined 34 published studies demonstrating that the MPVS is a reliable, valid, and psychometrically sound measure for capturing multiple facets of peer victimization across a variety of samples. Results also highlighted that there are relatively stable sex differences in the rates and pattern of peer victimization, with males experiencing more direct forms of victimization and females experiencing more indirect forms of victimization. Recommendations for further research are discussed, alongside new ways to further advance the assessment of peer victimization.